The Law of Medical Negligence: An Analysis of Pakistani Law and Shariah (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2025)
The present Pakistani legal system does not satisfactorily deal with the problem of medical negligence and the consequences it entails. It does neither provide justice to the medical doctors nor safety to the patients. The inconsistent verdicts emanating from the judiciary and quiet posture of the statutory laws have vexed the medical doctors groping to locate the dividing line between clinical and criminal. It does not differentiate unequivocally between the blatant incompetence and momentary errors committed by the medical doctors, and thus, renders leave them astray as the test for gross negligence does not make it clear to the medical practitioners what the law expects from them. This paper examines the law of medical negligence in Pakistan and points out the shortcomings comparing the Shariah and Pakistani Legal System.